Biocomputing 2020 2019
DOI: 10.1142/9789811215636_0063
|View full text |Cite
|
Sign up to set email alerts
|

Computationally efficient, exact, covariate-adjusted genetic principal component analysis by leveraging individual marker summary statistics from large biobanks

Abstract: The popularization of biobanks provides an unprecedented amount of genetic and phenotypic information that can be used to research the relationship between genetics and human health. Despite the opportunities these datasets provide, they also pose many problems associated with computational time and costs, data size and transfer, and privacy and security. The publishing of summary statistics from these biobanks, and the use of them in a variety of downstream statistical analyses, alleviates many of these logis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(18 citation statements)
references
References 21 publications
1
17
0
Order By: Relevance
“…This approximation method is described in detail in Ray & Boehnke (2018). Two of our previous papers (Gasdaska et al, 2019; Wolf et al, 2020) have demonstrated the accuracy of these three methods through both simulation and real-data applications.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…This approximation method is described in detail in Ray & Boehnke (2018). Two of our previous papers (Gasdaska et al, 2019; Wolf et al, 2020) have demonstrated the accuracy of these three methods through both simulation and real-data applications.…”
Section: Methodsmentioning
confidence: 99%
“…Further, Var. In a recent paper (Wolf et al, 2020), we demonstrated how to calculate these values using only PCSS: and where S ( X ) is the p × p variance-covariance matrix of the columns of the design matrix X , is the p × 1 vector of column means of X , is the mean of w m , and is the sample covariance between w m and x j .…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…This method is applicable to both continuous and binary traits. In addition, Wolf et al 2020 proposed an approach for continuous outcomes using summary statistics of outcomes and covariates derived from the same study 6 .…”
Section: Introductionmentioning
confidence: 99%